The University of Glasgow's Faculty of Divinity in the First World War. Issue 1 (April 2019) - Methuen, Charlotte; Firn, Annika; Henneberry, Alicia; Novotny, Jennifer
Abstract : How was the Divinity Faculty at the University of Glasgow affected by the First World War? This article draws on the University Archives and the lists of serving Divinity Students produced for the Church of Scotland's General Assembly to explore the stories of the Faculty of Divinity's staff and students (both current and potential), who joined up. It considers the way in which the Faculty adjusted to the depletions resulting from the War, as numbers of students dropped to a fraction of pre-War enrolments, and outlines the arrangements made by the Church of Scotland to allow Divinity Students who had served to complete their studies. Finally, it analyses the responses of the Glasgow Divinity professors to the General Assembly's recommendation that the Scotland's Divinity Faculties should combine resources with their sister United Free Church Colleges. This step of ecumenical, inter-presbyterian cooperation paved the way for the establishment of Glasgow's Trinity College after the 1929 Reunion.